Macrophage inhibitory cytokine-1 versus carbohydrate antigen 19–9 as a biomarker for diagnosis of pancreatic cancer: A PRISMA-compliant meta-analysis of diagnostic accuracy studies. Issue 9 (March 2018) - Yang, Ying; Yan, Shirong; Tian, Hui; Bao, Yixi
Abstract: Background: Because of the high malignant degree of pancreatic cancer (PC), the early diagnosis of PC is of great concern. Macrophage inhibitory cytokine-1 (MIC-1) was reported to be a potential diagnostic biomarker, but its diagnostic value is indeterminate. Therefore, we performed this meta-analysis to compare it to carbohydrate antigen 19–9 (CA19–9), the most frequently used serum biomarker in PC. Material and Methods: After a systematic review of the relevant studies, the pooled diagnostic indices, including sensitivity, specificity, positive/negative likelihood ratio (PLR/NLR), diagnostic odds ratio (DOR), summary receiver operating characteristic curve (sROC), and area under the SROC curve (AUC) were used to evaluate the diagnostic value of MIC-1 and CA19–9 for PC. These indices were pooled with random-effects models. We explored the heterogeneity by meta-regression. Results: Fourteen studies comprising a total of 2826 subjects were included in our meta-analysis. The summary estimates for MIC-1 and CA19–9 are listed as follows: sensitivity, 80% [95% confidence interval (CI) 78–82] versus 71% (95% CI 68–73); specificity, 85% (95% CI 83–87) versus 88% (95% CI 86–90); DOR, 24.57 (95% CI 14.00–43.10) versus 17.65 (95% CI 11.65–26.76); area under sROC (AUC), 0.8945 versus 0.8322; PLR, 5.18 (95% CI 3.24–8.26) versus 5.34 (95% CI 3.78–7.54); and NLR, 0.23 (95% CI 0.19–0.29) versus 0.32 (95% CI 0.28–0.37). Conclusion: These data demonstrate that serum MIC-1 has a comparable diagnostic accuracy to CA19–9 for PC.